The The Effect of Acupressure Method on Dysmenorrhea in Adolescent Woman at Muhammadiyah 1 Gresik Junior High School - Kasih, Ginanjar Anggita; Irawan, Dwi Dianita; sulistiyowati (International Journal of Natural and Health Sciences, 2024)
Adolescent girls are more susceptible to dysmenorrhoea which is influenced by many factors, one of which is the mental condition of adolescents who experience menstruation. The aim of the research was to analyze the effect of the acupressure method on dysmenorrhoea in young women at Muhammadiyah 1 Gresik junior high school. This research design uses the Pre-Experiment method with a One Group Pretest Posttest design. The population was 44 teenagers who experienced dysmenorrhoea, using the Simple Random Sampling technique, 40 teenagers were obtained. This data was taken using a questionnaire and Visual Analogue Scale (VAS) scores.  After tabulating the data, it was analyzed using the Paired t Test with a significance level of p = <0.05. The results of the study showed that the average dysmenorrhoea scale before the acupressure method was carried out was 5.6 and after the acupressure method was carried out it was 2.28.  Based on the results above, the significance value is sign=0.000<0.05. This means that there is an influence of the acupressure method on dysmenorrhoea in young women at Muhammadiyah 1 Gresik junior high school